Epidemiological study of common diseases and their risk factors in camels in South Punjab, Pakistan. (July 2017) - Durrani, Aneela Zameer; Bashir, Zubair; Rasheed, Imran; Sarwar, Noor-ul-Ain
Abstract: Bacteriological study of mastitis along with common blood protozoan diseases were studied in dromedary camels in Cholistan, Dera Ismail Khan and Rahim Yar Khan districts in South Punjab, Pakistan. For this purpose 300 camels were sampled randomly at different common grazing and watering point. For study of blood parasites clinically suspected and apparently healthy camels, 150 each, were sampled. An overall prevalence of 15%and 5% was recorded for trypanosomiasis and Anaplasmosis respectively. Trypanosoma evansi was identified with 280 bp product on polymerase chain reaction test. There was significant (P < 0.05) decline in the values of total erythrocyte counts, hemoglobin concentration, packed cell volume, serum total proteins and albumin while erythrocyte sedimentation rate was increased in infected camels as compared to healthy ones. Aspartate aminotransferase, alanine aminotransferase, gamma glutamyltransferase and alkaline phosphatase were also significantly increased in blood protozoan the infected animals. Milk samples for bacteriology were collected from healthy lactating camels (n = 100). Information about different risk factors were gathered on designed performa. Subclinical mastitis on surf field test was recorded in 42% camels while 2% cases of clinical mastitis were recorded. Staphylococcus aureus, Streptococcus agalactiae, Streptococcus dysgalactiae, Bacillus cereus and. Corynebacterium kutscheri were isolated with characteristic beta and alpha hemolysis patterns. Chi-square analysis showed significant difference as p < 0.05 among various species of bacteria (χ2 = 21.649, P-Value = 0.0001, df = 3). Antibiogram showed Gentamicin, Norfloxacin, Oxytetracycline as most effective therapy for mastitis in camel.